Vandalismo na escola: uma explicação pautada nos valores humanos, personalidade e desempenho acadêmico - Nunes, Jéssyca Cristina Ferreira (2021)
This dissertation indicated to know to what extent personality traits, human values and academic performance explain vandalism at school. So, two articles were made and the third has been making. In the First Article, a theoretical nature, was suggested to introduce the subject of vandalism at schools, distinguished by the act of destroying or precluded school spaces and objects, which may cause environmental and social damage. Article 2 dealt with the elaboration of the Vandalized School Conduct Scale (VSCS), gathering evidence of its psychometric properties. To that, two studies were carried out with samples of students from Middle High School. On first project (N = 200; Age = 13.8; SD = 1.51, 54% male), students answered the Vandalism Conduct Scale at School and socio demographic questions. An exploratory factor analysis indicated a two-factor structure, consisting by 24 items. In second project (Age = 13.7; SD = 1.71; 51.5% male), participants answered to ECVE with 14 items. A confirmatory factor analysis corroborated the two-factor structure: Acts of destruction (α = 0.71) and Disfigurement acts (α = 0.75) [CFI = 0.89 and RMSEA = 0.07 (CI90% = 0.05 - 0.08)]. Evidence attested to the adequacy of VSCS. On third article which explain school vandalism, dark personality features, human values and academic performance. Mainly, it was intended (1) to understand the relationship between school vandalism, personality features and human values and (2) to understand the role of evil personality features, human values and academic performance on explaining vandalism at school. For that, 400 Middle High School students participated (Age= 13.7; SD = 1.61; 52.8% male), they answered demographic questions and the following diligences: Vandalism at School Scale (VSS), Dark Triad Dirty Dozen (DTDD), Questionnaire of Basic Values (QVB) and Self-Assessment Scale of Academic Performance (SASAP). The consequence indicated that school vandalism was correlated with evil personality and its dimensions; supra personal values, normative values and satisfaction values; academic achievement. It was also found that the variables that best explained vandalism at school are the evil personality narcissism and psychopathy, academic performance and suprapersonal values. Before the exposed, we believe that the central objective was achieved, with the solution of diligences with suitable psychometric evidence, in addition to contributing to the understanding of vandalism at school.